1998
DOI: 10.2307/172249
|View full text |Cite
|
Sign up to set email alerts
|

Covert Contraceptive Use: Prevalence, Motivations, and Consequences

Abstract: This article examines women's covert use of contraceptives, that is, their use of a method without their husbands' knowledge. Three questions are addressed: (1) How is covert use measured? (2) How prevalent is it? and (3) What are the factors underlying covert use? Existing studies are used together with survey and qualitative data collected in 1997 in an urban setting in Zambia from married women and their husbands. Women's covert use of contraceptives is estimated to account for 6 to 20 percent of all curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 13 publications
3
154
2
Order By: Relevance
“…Correspondingly, the husband's approval of contraception was positively associated with contraceptive use in Ghana (Oheneba-Sakyi & Takyi, 1997) and with good communication between the spouses in previous studies (Oni & McCarthy, 1991;Oheneba-Sakyi & Takyi, 1997). Even if women have access to womancontrolled, covert methods of protection, discussion of contraceptive use with the primary male partner is likely (Biddlecom & Fapohunda, 1998;Castle et al, 1999;Green et al, 2001). Thus, it is widely believed that male involvement in family planning is necessary for improved contraceptive use (Sternberg & Hubley, 2004), and there is evidence that interventions targeting men have improved men's acceptance of contraception, including the use of condoms (Piotrow et al, 1992;Celentano et al, 1998;Laukamm-Josten et al, 2000;Leonard et al, 2000;Sternberg & Hubley, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…Correspondingly, the husband's approval of contraception was positively associated with contraceptive use in Ghana (Oheneba-Sakyi & Takyi, 1997) and with good communication between the spouses in previous studies (Oni & McCarthy, 1991;Oheneba-Sakyi & Takyi, 1997). Even if women have access to womancontrolled, covert methods of protection, discussion of contraceptive use with the primary male partner is likely (Biddlecom & Fapohunda, 1998;Castle et al, 1999;Green et al, 2001). Thus, it is widely believed that male involvement in family planning is necessary for improved contraceptive use (Sternberg & Hubley, 2004), and there is evidence that interventions targeting men have improved men's acceptance of contraception, including the use of condoms (Piotrow et al, 1992;Celentano et al, 1998;Laukamm-Josten et al, 2000;Leonard et al, 2000;Sternberg & Hubley, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…[18] Globally low SES is associated with poor and inconsistent contraceptive use. [17,19] Lower SES women, and particularly those in rural areas, have limited access to health services, which may limit their contraceptive access. [3,13] A number of difficulties may explain the the low CPR.…”
Section: Discussionmentioning
confidence: 99%
“…A Zambian study found that only 20% of men approved of contraceptive use, believing that contraception will prevent women having the number of children they desire. [19] The study involved a rural site that is a commercial farming area, unlike traditional rural areas where men are the decision makers, [14] which may explain our inconsistent finding. Injectables enable a woman to be on contraception without the knowledge of her partner.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31] Women can take injections of depo-provera while visiting a health facility and remain protected against unwanted pregnancies for three months. This may be done without their husband's knowledge and without the bother of having to remember to take the pill or to undergo clinical procedures that are involved when opting for implants or intrauterine devices.…”
Section: Discussionmentioning
confidence: 99%